ANALYSIS OF THE REALIZATION OF THE REGIONAL REVENUE AND EXPENDITURE BUDGET OF EAST BARITO REGENCY IN 2023-2024 IN SUPPORTING REGIONAL FINANCIAL EFFICIENCY - Anisa Noor Aulia; Tri Hidayati; Arif Mubarok; Muhammad Zainal Arifin (Universitas Muhammadiyah Bengkulu, 2026)
This study examines the realization of the Regional Revenue and Expenditure Budget (APBD) of East Barito Regency during 2023–2024 to assess its contribution to regional financial efficiency. While previous studies have largely focused on single-year evaluations, comparative multi-year analyses remain limited. This research addresses that gap by evaluating APBD performance using the Value for Money framework (economy, efficiency, and effectiveness). A descriptive qualitative approach was employed through data triangulation, including key informant interviews, non-participant observation, and validation of audited Local Government Financial Statements (LKPD). The findings reveal a significant improvement in fiscal performance in 2024. Revenue realization exceeded the budget target, reaching 101.22%, supported by increased transfer revenues. Expenditure absorption also improved, with overall spending realization of 92.22% and capital expenditure realization of 91.70%. In addition, the Budget Financing Surplus (SiLPA) decreased substantially from Rp154.28 billion in 2023 to Rp30.97 billion in 2024, indicating greater budgetary effectiveness and more efficient financial management